1991
DOI: 10.1128/jb.173.3.1051-1063.1991
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella typhimurium has two homologous but different umuDC operons: cloning of a new umuDC-like operon (samAB) present in a 60-megadalton cryptic plasmid of S. typhimurium

Abstract: Expression of the umuDC operon is required for UV and most chemical mutagenesis in Escherichia coli. The DNA which can restore UV mutability to a umuD44 strain and to a umuC122::Tn5 strain of E. coli has been cloned from Salmonella typhimurium TA1538. DNA sequence analysis indicated that the cloned DNA potentially encoded proteins with calculated molecular weights of 15,523 and 47,726 and was an analog of the E. coli umuDC operon. We have termed this cloned DNA the samAB (for Salmonella mutagenesis) operon and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
64
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 64 publications
0
64
0
Order By: Relevance
“…In Salmonella typhimurium, a plasmid-borne homolog of Pol V called SamAB has been described. 47 A BLAST analysis of the UTI89 genome for Pol V homologs suggested such a factor, annotated as encoded by the open reading frames impCA, may be present on the megaplasmid. We did not find any in vitro and in vivo genetic evidence for an active role of Pol V or ImpC/ImpA proteins in pathogenicity and mutability of UPEC UTI89 strain.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…In Salmonella typhimurium, a plasmid-borne homolog of Pol V called SamAB has been described. 47 A BLAST analysis of the UTI89 genome for Pol V homologs suggested such a factor, annotated as encoded by the open reading frames impCA, may be present on the megaplasmid. We did not find any in vitro and in vivo genetic evidence for an active role of Pol V or ImpC/ImpA proteins in pathogenicity and mutability of UPEC UTI89 strain.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Furthermore, introduction of E. coli recA into S. typhimiariiam did not increase induced mutability, suggesting that poor mutagenesis was not based on a limitation of S. typhimurium RecA action (unpublished observation). Different mutagenic potencies are also seen when cloned examples of uimu-like genes are introduced into E. coli (4,30,37) or when miucAB enhanced the low levels of mutagenesis of many of the species examined here (35). Thus, lama operons from different sources may have different mutagenic potencies inherent in their sequences.…”
mentioning
confidence: 99%
“…Nevertheless, mutagenesis relying on SOS induction was demonstrated in S. typhimurium (31), and it was ultimately shown that S. typhimurium does indeed have a chromosomal umuDC operon despite all the previous indications to the contrary (44,45,48,49). In fact, S. typhimurium LT2 contains two umuDC-like operons; the second, designated samAB, is encoded by the cryptic LT2 plasmid (30).…”
mentioning
confidence: 99%
See 2 more Smart Citations